Influence of extra chromium addition on the microstructure, hardness, and corrosion behaviour of high carbon ferrochrome FeCrV15 deposited through laser cladding on steel baseplate for tillage application. (24th November 2021) - Aramide, Basiru; Popoola, Patricia; Sadiku, Rotimi; Jamiru, Tamba; Pityana, Sisa
Abstract: Laser cladding is an additive manufacturing technology utilised in surface strengthening, modification, and repair of components subjected to adverse working conditions, such as tillage tools, which is accomplished by adding functionally graded material with a remarkable limit to enhancing an engaged credited property of monolithic material that is superior and better than its monolithic counterparts. In this comparative study, FeCrV15 and FeCrV15 + Cr deposits were deposited on steel baseplate through Laser Additive manufacturing (laser cladding), and the hardness, microstructure and corrosion behaviour of the developed samples were examined and compared. The effect of extra addition of chromium on the corrosion behaviour of the high carbon ferrochrome FeCrV15 in 3.5 wt% NaCl solution was investigated. The morphologies of the microstructures were analysed with the Scanning Electron Microscope equipped with Energy Dispersion Spectroscopy (SEM/EDS), Optical microscope, x-ray diffractometer and Vicker microhardness tester. The result shows that extra chromium addition greatly influences the hardness, microstructural formation and corrosion behaviour of high carbon ferrochrome FeCrV15.